Sick leave and return to work after surgery for type II SLAP lesions of the shoulder: a secondary analysis of a randomised sham-controlled study - Jens Ivar Brox; Øystein Skare; Petter Mowinckel; Jostein Skranes Brox; Olav Reikerås; Cecilie Piene Schrøder (BMJ Open)
Objectives To compare days on sick leave and assess predictors of return to work following shoulder surgery.Design A secondary analysis of a randomised controlled trial.Setting Orthopaedic department.Participants 114 patients with type II superior labral tear from anterior to posterior of the shoulder.Interventions Labral repair, biceps tenodesis or sham surgery.Outcome measures Sick leave was obtained from national registers for the last year before and 2 years following surgery. Total and shoulder related number of days on sick leave were obtained, using international diagnostic codes. We applied the difference-in-difference approach to compare the differences in the change in mean work days on sick leave between groups over time, backwards logistic regression and lasso regression to evaluate predictors.Results Mean total number of work days on sick leave during the 2 years after surgery was 148 (range 0–460) days. More than 80% of the sick leave days were taken by 22% of the patients. Days on sick leave classified as shoulder-related constituted 80% of the total. In all three treatment groups, the mean total number of days on sick leave doubled the year after surgery. Sham surgery and labral repair had fewer postoperative sickness absence days compared with biceps tenodesis but differences were not significant when adjusted for days of sick leave the year before surgery. Predictors of return to work at 2 years analysed by logistic regression were no sick leave (OR 8.0, 95% CI 2.4 to 26.0) and moderate symptoms of anxiety or depression (OR 0.16, 95% CI 0.05 to 0.5) at inclusion. Similar results were obtained by lasso regression but manual work was an additional predictor.Conclusions Change in mean work days on sick leave comparing sham surgery, labral repair and biceps tenodesis, was not significantly different. Sick leave, symptoms of anxiety and depression, and manual work at inclusion predicted work status 2 years after surgery.Trial registration number NCT00586742.